New Insights into Endothelin Signaling and Its Diverse Roles in the Retina - Schmitt, Sabrina I.; Bielmeier, Christina B.; Braunger, Barbara M. (Springer, 2019)
The vasoactive peptide endothelin is an effective regulator of blood pressure and vascular homeostasis. In addition, the dysregulation of the endothelin signaling pathway is discussed to contribute to ocular diseases like glaucoma or diabetic retinopathy. Furthermore, our workgroup and others showed a protective effect of endothelin 2 for the survival of photoreceptors. In this study, we analyzed mRNA expression levels of the endothelin signaling family in wild-type mice after a puncture of the eye, intravitreal PBS injections, or light-induced photoreceptor degeneration. We observed elevated endothelin receptor a (Eta), endothelin receptor b (Etb), endothelin 1(Et1), and endothelin 2 (Et2) levels, while endothelin 3 (Et3) mRNA levels were not significantly altered. Our findings indicate an important role of the endothelin signaling pathway in response to ocular trauma or disease. These findings make endothelin signaling a promising target to attenuate retinal degeneration.
CRIS-Team Scopus Importer:2023-04-11
Keywords: Endothelin; Endothelin receptor; Intravitreal injection; Light-induced damage; Neuroprotection; Photoreceptor damage